Human α4β2 Nicotinic Acetylcholine Receptor as a Novel Target of Oligomeric α-Synuclein - Liu, Qiang; Emadi, Sharareh; Shen, Jian-Xin; Sierks, Michael R.; Wu, Jie (PLOS ONE, 2013)
Cigarette smoking is associated with a decreased incidence of Parkinson disease (PD) through unknown mechanisms. Interestingly, a decrease in the numbers of α4β2 nicotinic acetylcholine receptors (α4β2-nAChRs) in PD patients suggests an α4β2-nAChR-mediated cholinergic deficit in PD. Although oligomeric forms of α-synuclein have been recognized to be toxic and involved in the pathogenesis of PD, their direct effects on nAChR-mediated cholinergic signaling remains undefined. Here, we report for the first time that oligomeric α-synuclein selectively inhibits human α4β2-nAChR-mediated currents in a dose-dependent, non-competitive and use-independent manner. We show that pre-loading cells with guanyl-5′-yl thiophosphate fails to prevent this inhibition, suggesting that the α-synuclein-induced inhibition of α4β2-nAChR function is not mediated by nAChR internalization. By using a pharmacological approach and cultures expressing transfected human nAChRs, we have shown a clear effect of oligomeric α-synuclein on α4β2-nAChRs, but not on α4β4- or α7-nAChRs, suggesting nAChR subunit selectivity of oligomeric α-synuclein-induced inhibition. In addition, by combining the size exclusion chromatography and atomic force microscopy (AFM) analyses, we find that only large (>4 nm) oligomeric α-synuclein aggregates (but not monomeric, small oligomeric or fibrillar α-synuclein aggregates) exhibit the inhibitory effect on human α4β2-nAChRs. Collectively, we have provided direct evidence that α4β2-nAChR is a sensitive target to mediate oligomeric α-synuclein-induced modulation of cholinergic signaling, and our data imply that therapeutic strategies targeted toward α4β2-nAChRs may have potential for developing new treatments for PD.